Selecting a College Academic Branch- a Design Decision Taking System for Student Career Selection - Balasubramanyam, S.; Padmaja Usharani, D.; Harsha Vardhan Reddy, A.; Swetha, Danthala; Narendra Santosh Kumar, Gurram; Anusha, K.; Hasane Ahammad, Sk. (International Journal of Engineering and Technology, 2018)
Â Student advising is an important task that every advisor must participate for his/her career. This paper defines the essentiality of the software, decision taking system for students to select their academic branch interests. By developing this software student interact with the system and specifies their interested jobs and based on their interests the system gives some suggestions from these suggestions the student should take decision in choosing their academic branch. A research is conducted by certain students in university, a set of questionnaires are given to students which asks about their interests and career possibilities. Set of results were taken by considering these questionnaires and compared with the results of computer system, a drastic change in the results was observed. The results obtained when students interacting with computer system are more efficient than the questionnaires given by the counselors. The computer system which is developed is more efficient when compared to manual counseling which takes more time to interact with students and analyze the results and say the correct career which a student has to choose.Â Â